2022
DOI: 10.1177/00302228221074160
|View full text |Cite
|
Sign up to set email alerts
|

Living Authentically in the Face of Death: Predictors of Autonomous Motivation Among Individuals Exposed to Chronic Mortality Cues Compared to a Matched Community Sample

Abstract: Despite research demonstrating positive outcomes of conscious death reflection, very little research directly examines a core proposition of existential psychologists—that death reflection provides an opportunity for more authentic living. The current study compared individuals chronically exposed to genuine mortality cues (funeral/cemetery workers, n = 107) to a matched control sample ( n = 121) on autonomous motivation. It also assessed the moderating role of six constructs implicated in growth-oriented proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Complementary research has shown that people with higher self-esteem function better in stressful occupations (e.g., Orth & Robins, 2014;Solomon et al, 1991b). Further, some evidence indicates that occupations in which workers are exposed to death (e.g., funeral/cemetery workers, doctors) or life-threatening situations (e.g., firefighters, police officers) may have a positive impact on workers, such as psychological flexibility (Arena et al, 2022), a loss of the fear of death (Arslantürk et al, 2021), increased levels of working safely (Yuan et al, 2018) and improved job performance (Perez-Floriano and Gonzalez, 2019). 5 Finally, improved active shooter training will require simulators and will need to be frequent to ingrain terror management mechanisms in each officer.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary research has shown that people with higher self-esteem function better in stressful occupations (e.g., Orth & Robins, 2014;Solomon et al, 1991b). Further, some evidence indicates that occupations in which workers are exposed to death (e.g., funeral/cemetery workers, doctors) or life-threatening situations (e.g., firefighters, police officers) may have a positive impact on workers, such as psychological flexibility (Arena et al, 2022), a loss of the fear of death (Arslantürk et al, 2021), increased levels of working safely (Yuan et al, 2018) and improved job performance (Perez-Floriano and Gonzalez, 2019). 5 Finally, improved active shooter training will require simulators and will need to be frequent to ingrain terror management mechanisms in each officer.…”
Section: Discussionmentioning
confidence: 99%